Incidence of Acute Kidney Injury in Autologous Hematopoietic Stem Cell Transplant Recipients According to the Administration of Empirical Amikacin: A Two-Centre Retrospective Cohort Study - Schürch, Sophie; Dräger, Sarah; Hoffmann, Michèle; Bausch, Severin; Gürtler, Nicolas; Hirzel, Cédric; Passweg, Jakob; Bassetti, Stefano; Pabst, Thomas; Sendi, Parham; Osthoff, Michael (Antibiotics (Basel), 2025)
Background: The benefit of adjunctive aminoglycosides in the treatment of patients with febrile neutropenia (FN) is controversial. We investigated the incidence of acute kidney injury (AKI) in patients with FN or suspected infection according to empirical amikacin treatment. Methods: This two-centre, retrospective cohort study was conducted at the University Hospitals of Basel (amikacin group) and Bern (non-amikacin group), Switzerland, between 2016 and 2022. Adult patients requiring antibiotic treatment after autologous hematopoietic stem cell transplantation (HSCT) were included. All patients received empiric beta-lactam treatment combined with amikacin in the amikacin group (only University Hospital Basel). The primary endpoint was the incidence of AKI within seven days after the initiation of antibiotic treatment. Results: Overall, 250 patients were included. The majority was male (n = 163, 65.2%) and had a median age of 61 years (interquartile range (IQR) 55 to 67). The median baseline eGFR was similar in both groups (>90 mL/min/1.7 m2). There was no statistically significant difference in the incidence of AKI (4/125 vs. 5/125, p = 1.0). The maximum decline in eGFR from baseline within 7 days was significantly higher in the amikacin group (−4 mL/min/1.7 m2 (IQR 8 to −12) vs. −2 mL/min/1.7 m2 (IQR −7 to −1), p = 0.001). Two patients suffered from an infection with an extended spectrum beta-lactamase producing (ESBL) pathogen. Conclusions: Amikacin treatment did not significantly impact the incidence of AKI in patients undergoing autologous HSCT. The short-term administration of amikacin in patients with normal to high baseline eGFR is safe regarding renal function. However, in a low-resistance setting, the omission of empirical amikacin treatment should be considered.